Analisis Strategis Atas Determinasi yang Mempengaruhi Kinerja Pegawai pada Unit Program Belajar Jarak Jauh - Bz, Fazli Syam; Musliadi, Musliadi (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2022)
Human resource is an important key for institutions and organizations. Good employee performance is the expectation of every institution including UPBJJ-UT Banda Aceh to be able to survive in a competitive working environment and to be able to provide maximum service. This study aimed to analyze the determination that affects employee performance at UPBJJ-UT Banda Aceh. This research was conducted on all employees of UPBJJ-UT Banda Aceh, with a population of 33 people. The independent variables in this study are salary, facilities, and leadership, while the dependent variable is employee performance. Apart from these two variables, this study used one intervening variable, that is motivation. The research instruments used are questionnaires, observation, and literature study. This research used descriptive statistical analysis and path analysis. The software used to process the data was SPSS 24. The finding of the research showed that: 1) Salary had a significant effect on the motivation of UPBJJ-UT Banda Aceh employees, 2) Facilities had no significant effect on the motivation of UPBJJ-UT Banda Aceh employees, 3) Leadership had a significant effect on the motivation of UPBJJ-UT Banda Aceh employees, 4) Salary had no significant effect on the performance of UPBJJ-UT Banda Aceh employees, 5) Facilities had no significant effect on the performance of UPBJJ-UT Banda Aceh employees, 6) Leadership had no significant effect on the performance of UPBJJ-UT Banda Aceh employees, and 7) Salary and leadership, mediated by motivation factor, affect employee performance significantly